Factors Affecting mobile Learning Readiness Among Students and Lecturers: A Model for Mobile Learning Readiness in Kenyan Universities - Ogamba, Stanley Mogaka; Peters, Ikhoa Anselemo (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Mobile learning plays an important role in developing both learning and teaching approaches in institutions of higher learning. However, a successful implementation of mobile learning strategies in Kenyan universities will largely be affected by users’ readiness to adopt and use this technology. Despite the effort by the Government of Kenya through the Ministry of Education, Science & Technology to encourage the use of technology in improving access to knowledge and skills in learning institutions, most learners and instructors have not sufficiently embraced this innovation. The purpose of the study was to determine m-learning readiness in the Kenyan Universities and create a model for adoption by these Universities. The purpose of this paper is to examine factors that affect the adoption of mobile technologies usage on mobile learning readiness among learners and instructors in Kenyan universities. A multiple regression analysis model was used to analyze the data collected from 555 participants (363 university students, 173 lecturers, and 19 heads of departments). The results of the study show that attitude, perceived ease of use, perceived usefulness, device type, m-learning content, internet availability, internet affordability, user expertise and institutional ICT strategy significantly influence the ability to use mobile devices and mobile learning readiness. The results of this research provide practitioners, educators and policy makers with meaningful insight into designing an appropriate m-learning model that supports the use of technology in Kenyan universities.